Adverse Cutaneous Drug Reactions With Special Reference To Non-Steroidal Anti Inflammatory Drugs In A Tertiary Care Hospital In Tamilnadu-South India - E. MANIVANNAN,; M. SHANTHI, (International Journal of Pharma and Bio Sciences, 2012)
The main objective of the paper is to find out the prevalence, to identify the probable causative agents and contributing factors. Cutaneous drug reactions (CDR) were prospectively among dermatological outpatients from August 2003 to September 2005. The total numbers of patients studied were 37,864. Drug history with clinical examination was done. The type of lesions with duration, age, sex, those patients who brought the offending drugs and reactions due to the particular drug were studied.. CDR was seen in 117 patients (1.1%) more in women, and in areas (face, trunk, extremities). The patterns of reactions were fixed drug eruptions (FDE) (74.36%), Utricaria (11.11%), The drugs incriminated were paracetamol (69.27%), diclofenac sodium (8.51%).. The clinical patterns and drugs causing CDR are similar as other parts of the country except for minor variations. It is obvious that the CDR and drugs causing such reactions are changing every year which may be due to the emergence of newer molecules